Asian longhorned tick, Haemaphysalis longicornis Neumann (Arachnida: Acari: Ixodidae) - Yuexun Tian; Phillip E Kaufman (EDIS, 2020)
The Asian longhorned tick, Haemaphysalis longicornis Neumann, also known as the longhorned tick, bush tick (Australia), and cattle tick (New Zealand), is a three-host tick native to East Asia. This tick has been categorized as an invasive species in Australia, New Zealand, and several Pacific Islands. In the U.S., an Asian longhorned tick infestation was recorded in New Jersey during the fall of 2017. This tick is somewhat unique in that females are capable of parthenogenesis, meaning that females can produce offspring without having mated with males. The Asian longhorned tick feeds on a wide range of hosts including birds and mammals, including humans. This tick is considered a medical and veterinary vector due to its ability to transmit pathogens that cause disease in humans and other animals. https://edis.ifas.ufl.edu/in1263